Modern community care strategies for schizophrenia care: Impacts on outcome - Burns, T (Springer New York, 2010)
Schizophrenia has been at the centre of psychiatry's development. The severity of schizophrenia's disabilities, in both its acute and more long-term phases, ensures its dominance in service planning. Self-neglect, apathy and disability derived from negative symptoms and cognitive dysfunction require social care and support as a central part of services. For practical purposes this means that the history and configuration of psychiatric services are broadly equivalent to the history and configuration of schizophrenia services. © Springer Science+Business Media, LLC 2010.